Answer:
1. m∠1 = 45°
2. m∠1 = 129°
3. m∠1 = 37°
4. m∠1 = 88°
m∠2 = 42°
m∠3 = 113°
5. m∠1 = 62°
m∠2 = 45°
m∠3 = 24°
6. m∠1 = 128°
m∠2 = 52°
m∠3 = 47°
m∠4 = 133°
7. m∠1 = 41°
m∠2 = 85°
m∠3 = 95°
m∠4 = 85°
m∠5 = 36°
m∠6 = 50°
m∠7 = 107°
8. x = 9°
10. x = 5°
11. x = 7°
Explanation:
1. m∠1 = 180° - (76° + 59°) = 45°
m∠1 = 45°
2. m∠1 = 62° + 67° = 129°
m∠1 = 129°
3. m∠1 = 152° - 115° = 37°
m∠1 = 37°
4. m∠2 = 42° (Alternate angles)
m∠1 = 180° - (50° + m∠2) = 180° - (50° + 42°) = 88°
m∠1 = 88°
m∠3 = 180° - (25° + 42°) = 113°
m∠3 = 113°
5. m∠3 = 73° - 49° = 24°
m∠3 = 24°
m∠2 = 118° - 73° = 45°
m∠2 = 45°
m∠1 = 180° - (73° + 45°) = 62°
m∠1 = 62°
6. m∠2 = 52° (Alternate interior angles)
m∠1 = 180° - 52° = 128° (The sum of angles on a straight line)
m∠1 = 128°
m∠3 = 47° (Alternate interior angles)
m∠4 = 180° - 47° = 133° (The sum of angles on a straight line)
m∠4 = 133°
7. m∠3 = 95° (Vertically opposite angles)
m∠2 = m∠4 (Vertically opposite angles)
m∠3 + 95° + m∠2 + m∠4 = 360° (The sum of angles at a point)
2 × 95° + 2 × m∠2 = 360°
m∠2 = (360° - 2 × 95°)/2 = 85°
m∠2 = 85° = m∠4
m∠2 = 85°
m∠4 = 85°
m∠1 = 360° - (85° + 140° + 90°) = 41°
m∠1 = 41°
m∠5 = 180° - 144° = 36°
m∠5 = 36°
m∠6 = 180° - (m∠5 + m∠3) = 180° - (36 + 95°) = 50°
m∠6 = 50°
m∠7 = 360° - (m∠4 - 38° - (180° - m∠6)) = 360° - (85° - 38° - (180° - 50°)) = 107°
m∠7 = 107° (Sum of angles in a quadrilateral)
8. (10·x - 11)° + (3·x - 2)° + (3·x + 1)° = 180°
Using an online application, we have;
(6·x - 12)° = 180°
x = (180 + 12)°/6 = 32°
x = 32°
9. (3·x - 5)° + (7·x + 5)° + 90° = 180°
Using an online application, we have;
10·x = 180° - 90° = 90°
x = 90°/10 = 9°
x = 9°
10. 151° = (11·x - 1)° + (20·x - 3)°
151° = 31·x - 4°
31·x = 151° + 4° = 155°
x = 155°/31 = 5°
x = 5°
11. (14·x - 13)° = (4·x + 13)° + (6·x + 2)°
(14·x - 13)° = (10·x + 15)°
(14·x - 10·x)° = (13 + 15)° = 28°
4·x = 28°
x = 28°/4 = 7°
x = 7°